Eksekusi Terhadap Benda Jaminan Fidusia Yang Tidak Didaftarkan Pada PT. Capella Multidana - Muhammad Ikhsan Awaljon Putra; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Fiduciary insurance is widely used by financial institutions, fiduciary regulated in Law Number 42 Year 1999 regarding Fiduciary. Article 11 (1) of the Act Fiduciary stating that the object burdened with the fiduciary must be registered.In practice on PT. CapellaMultidana in Pekanbaru was also a fiduciary guarantee object that is not registered in Fiduciary Registration Office, it is contrary to Article 11 (1) of the Act Fiduciary. Issues that will be examined in this study are: First, What is the legal effect of the fiduciary object that is not registered to the Registration office Fiduciary by PT. Capella Multidana? Secondly, How the execution of fiduciary objects that are not registered with the registration office Fiduciary by PT. Capella Multidana?This type of research used socio-juridical namely the workings of law in society. Descriptive nature of this study. This research was conducted at PT Capella Multidana Finance in Sudirman Street No. 414 Pekanbaru. The source data of this research is first, primary data that the debtor and the PT. Capella Multidana. Second, secondary data related law, literature, books, encyclopedias and dictionaries. Population and sample is the debtor and the PT. Capella Multidana. Data collection techniques are the First, interviews with the debtor and the Capella Multidana. Secondly, the questionnaire with the debtor PT. Capella Multidana. Third, the literature contained in books and literature.The results obtained in this study is first, not the registration of the legal consequences of fiduciary objects made by PT. Capella Multidana is not able to do the execution, Second, execution of object fiduciary conducted by PT. Capella Multidana Finance can not give legal certainty to the parties. All of that, because PT. Capella Multidana never register the object so that the object fiduciary fiduciary should not be done.Based on the research results, there are two basic problems that can be inferred. First, the result of an agreement with fiduciary law that are not registered are not able to do the execution. Second, the execution of fiduciary objects that are not registered can not give legal certainty to the parties. Suggestions writer, first, that the object must be registered to fiduciary Fiduciary Registration Office by the finance company, so the lack of legal certainty among the parties. Second, that there must be enforcement of the executions carried out by the finance company to the object of fiduciary collateral object is not registered with the Registry Office fiduciary.